Discovery and genesis mechanism of high content diamondoids in the Gulong shale oil - Xuefeng Bai; Zihui Feng; Xiaochang Zhang; Qiuli Huo; Wei Jin; Jing Sun; Huasen Zeng (Scientific Reports)
Abstract Diamondoids are an important industrial material for biomedicine and equipment manufacturing. In addition to chemical synthesis methods used in industry, direct separation from petroleum is also a potential approach. Therefore, studying the quantity and formation mechanism of diamondoids in crude oil has attracted attention. The Gulong shale oil in the Songliao Basin is accumulated in-situ and has not been affected by migration, fractionation, or biological modification; therefore, it provides a natural laboratory for studying the genesis of diamondoids. This article explores the content and formation mechanism of diamondoids in Gulong shale oil through absolute quantification and chromatography-mass spectrometry analysis techniques. The results show that (1) the total diamondoid content in the Gulong shale oil is 45–1,059 µg/g, including 45–1005 µg/g of adamantane and 0–53 µg/g of diamantane. The maximum diamondoid content in shale oil is about 10 − 20 times that in conventional oil. (2) The content of diamondoids in shale oil is controlled by thermal evolution with thermal maturity at Ro < 0.8%, 0.8%−1.2%, 1.2%−1.4%, and > 1.4%, the diamondoid content exhibits four changing characteristics: low value, essential stability, slow increase, and rapid increase, respectively, indicating that the shale oil has undergone rearrangement, cracking, and other reactions to form diamondoids under high temperatures and pressures. (3) The content of diamondoids in shale oil is closely related to the catalytic effect of clay minerals; the diamondoid content in shale oil with high thermal maturity is 1.26 − 1.35 times higher than that in tight oil, confirming that the catalytic effect of clay minerals in shale is conducive to the formation of diamondoids. (4) The content of diamondoids in shale oil is significantly affected by reservoir pressure; under high thermal maturity, the shale oil with a reservoir pressure coefficient of 1.5 has a higher diamondoid content than that with a pressure coefficient of 1.3 by 1.4 times. In particular, the appearance of diamantane implies that high-pressure conditions are favorable for the formation of high-grade diamondoids. Finally, a formation and evolution model of diamondoids in the Gulong shale oil was established, which shows four stages with different formation mechanisms, including primary, inheritance, generation, and enrichment.